Analyzing Customer Perception Toward the Existence of Dance Agency in Bandung (Case Study of Wanna Be Pro Dancer) - Ayudyaputri, Ratih; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract: The researcher will try to Dance is the art of movement of the body, usually rhythmically, improvised steps and gestures. Children to adults prefer the art of dance. In dynamic and modern society, the trend changes rapidly and it makes the competition in Dance Industry become higher. Nowadays, many Indonesian people being a multitalented which they think needs to develop their talents, gain experiences and famous with join a dance agency. The objective of this research is to identify the customer perception of dance agency in Bandung. While, Wanna be Pro be ranked as the first established and best dance studio in Bandung. Then, this research will assist Wanna be Pro in finding what Wanna be Pro should develop or repair in gaining a better performance in the business.